Correspondence Between Renormalized and Entropy Solutions to the Parabolic Initial-Boundary Value Problem Involving Variable Exponents and Measure Data (Journal of Nonlinear Modeling and Analysis, 2025)
We study the initial-boundary value parabolic problem involvingvariable exponent under the generalized Leray-Lions conditions. We clarifythe definitions of entropy and renormalized solutions to such parabolic problems, and we establish the equivalence between these definitions of entropyand renormalized solutions to the parabolic problems with the Leray-Lionsoperator and with measure data.